Purification and Characterization of Monazite from Bangka using Mechanical-Magnetic Separation Method - Herman Aldila; Anisa Indriawati; Permono Adi Putro (Postgraduate, University of Mataram, 2024)
In this research, the purification and characteristics of monazite, a by-product of the tin ore enrichment process. Monazite is given pre-treatment to monazite sand using the mechanical-magnetic separation method to increase the content of rare earth metal elements. Based on the results of the analysis of monazite samples from Tin mine tailings concentrate that has been purified, the dominant elements of the highest rare earth metals are cerium (Ce), lanthanum (La), neodymium (Nd), and Yttrium (Y). The mechanical-magnetic separation method, monazite from Tin mine tailings concentrate can have higher purity. These rare earth metal elements can be further extracted or synthesized; and used as supporting or even main materials in developing advanced technological industries.